Population Density of Kloss’s Gibbon (Hylobates klossii) at Bojakan Resort, Siberut Island, West Sumatra: KEPADATAN POPULASI BILOU (Hylobates klossii) DI RESORT BOJAKAN, PULAU SIBERUT, SUMATERA BARAT - Vallen Sakti Maulana; Ani Mardiastuti; Entang Iskandar; Jansen Manansang (Media Konservasi, 2019)
Kloss’s gibbon (Hylobates klossii) is endemic primate to the Mentawai Islands of the West Sumatra, and currently categorized as Endangered according to IUCN Red List in 2008. The latest population information on Siberut Island is incomplete and not comprehensive yet. Assessment of population was used as a base in determining the conservation strategies. This study aimed to identify the Kloss’s gibbon population that includes population distribution, individual and group density, group size, and group composition. This research was conducted in Bojakan Resort, Siberut National Park, Siberut Island, Mentawai Islands, West Sumatra. Surveys for primates were carried out between November 2018 and Januari 2019. Following previous primate surveys and general recommendations, this study used line transect sampling. Total Kloss’s gibbon individuals found were 77 individuals with 25 groups. Average individual density was 12,8 individuals km2, group density was 4,2 groups km2, and group size was 3,08 individuals group. Kloss’s gibbon populations was affected by disruption of human activity. Kloss’s gibbon density in Bojakan Resort was higher compared to previous studies on Siberut Island. The percentage of Kloss’s gibbon groups that have a group size of more than two individuals was higher than the group of two individuals, indicating that forests in Bojakan Resort was abble to support the Kloss’s gibbon population. There were many groups that have at least one or more offspring, a good sign that regeneration progress was still ongoing. Monitoring and patrolling by National Park is needed to ensure the existence of the Kloss’s gibbon population in that area. Keywords: endemic primate, kloss’s gibbon, line transect sampling, monogamy